2020
DOI: 10.1002/celc.201901860
|View full text |Cite
|
Sign up to set email alerts
|

MOF‐Derived Copper Nitride/Phosphide Heterostructure Coated by Multi‐Doped Carbon as Electrocatalyst for Efficient Water Splitting and Neutral‐pH Hydrogen Evolution Reaction

Abstract: Efficient and robust electrocatalysts composed of earth‐abundant elements to replace noble metals is highly essential for cost‐effective production of hydrogen from water splitting. Herein, we demonstrate the fabrication of SO42− anions bridged MOF‐derived Cu3N−Cu3P heterostructure coated by ultrathin N, P, S‐tri‐doped carbon (NPSC) on nickel foam (Cu3N−Cu3P/NPSCNWs@NF) via an interface reconstruction strategy. The first‐principle simulation demonstrates that both Cu3N, Cu3P and NPSC own good electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“… S. no. Electrocatalyst Tafel slope (mV/dec) References 1 Cu 3 N-Copper foam 168 38 2 Cu 3 N-Nickel Foam 122.06 43 3 Cu 3 N-Cu 3 P-Nickel foam 69 44 4 Cu 3 N-PdO 122.83 45 5 Cu 3 N-NF 122 46 6 Cu 2 O-C 3 N 4 55.0 47 7 Cu3P-CoP nanowire 96 48 8 Cu 2 O 77.35 This work 9 Cu 3 N 63.28 This work …”
Section: Resultsmentioning
confidence: 99%
“… S. no. Electrocatalyst Tafel slope (mV/dec) References 1 Cu 3 N-Copper foam 168 38 2 Cu 3 N-Nickel Foam 122.06 43 3 Cu 3 N-Cu 3 P-Nickel foam 69 44 4 Cu 3 N-PdO 122.83 45 5 Cu 3 N-NF 122 46 6 Cu 2 O-C 3 N 4 55.0 47 7 Cu3P-CoP nanowire 96 48 8 Cu 2 O 77.35 This work 9 Cu 3 N 63.28 This work …”
Section: Resultsmentioning
confidence: 99%
“…Copper-based MN materials including their hybrids with bimetallic [ 237 ], oxynitride [ 237 ], carbonate hydroxides [ 238 ], and metal phosphides [ 239 ] have also proven to be efficient catalysts for HER. In one of the reports, it was demonstrated that the addition of Co-Ni carbonate hydroxides on Cu 3 N, which has a 3D hierarchical structure, significantly lowers the overpotential and the Tafel slope, demonstrating excellent HER activity.…”
Section: Electrochemical Production Of Hydrogenmentioning
confidence: 99%
“…17 Similarly, Cu-MOF and Ni-MOF were used to derived Cu 3 N−Cu 3 P heterostructure and Ni 3 N, respectively for HER application. 18,19 Li et al have worked on the utilization of MOFs for preparing carbon composites (Co-N x /C). 20 This homogeneous mixture of Co-N x and C exhibited good electrocatalytic activity toward OER.…”
Section: Introductionmentioning
confidence: 99%